Stadtgeographien an der Schwelle zwischen Nord und Süd: Globale Bewegungen und territoriale Ordnung in Ciudad Juárez, Mexiko - Berndt, Christian (ERDKUNDE, 2004)
Just like other southern cities Ciudad Juárez is a laboratory for the deeply contradictory nature of a development strategy which aims to initiate modernization processes though the integration into global production and consumption networks. Sharing the critique of globalization pessimists on the social reality in Juárez, the paper seeks to analyze the conditions allowing the rhetoric of modernization to achieve its powerful impact on people's everyday lives. A complex governance regime has been established which works with temporal and spatial borders, flexibly mapping a contradictory city of movement and stability. This is made visible from a methodological position that approaches the city from the perspective of human actors and processes of social organization. Discarding traditional conceptualizations of the city as a territorial entity, the paper therefore investigates Juárez from three different angles. Section 2 conceptualizes Juárez as de-limited city, the focus being on its role as facilitator of global economic flows, rather than on the securing of economic returns to place. Looking at the practice of powerful local interest groups and their efforts to channel and control the movements of people in the city, section 3 portrays Juárez as a flexibly territorialized configuration, traversed by multiple borders. Section 4 looks at the Juárez lived by ordinary migrant workers and charts a translocal city in movement, a city which defies the ordering strategies of powerful economic and political elites. Taken together, these three approaches compose a multi-perspectival picture of a city, realizing itself in plurilocal networks. It is in this way that Juárez stands as exemplary for the ambivalent realities of urbanity and urbanization that characterize our global age.